(untitled) (Journal of Pathology of Nepal, 2020)
Undifferentiated carcinoma of pancreas with osteoclastic giant cells is a rare tumor. The prognosis is slightly better than usual anaplastic carcinoma. It is said to have an epithelial origin. We present a case of 61-year-old female who presented with features of cholangitis and on evaluation found to have pancreatic mass. Pancreatic intraepithelial neoplasia was also present in our case, which is a feature less commonly noted in published literature.